Environmental Stress Responses of DnaJA1, DnaJB12 and DnaJC8 in Apis cerana cerana - Li, Guilin; Zhao, Hang; Zhang, Xuemei; Zhang, Yanming; Zhao, Huayu; Yang, Xinxin; Guo, Xingqi; Xu, Baohua (Frontiers in Genetics, 2018)
DnaJ, also known as Hsp40, plays important roles in maintaining the normal physiological state of an organism under stress conditions by mediating essential processes, such as protein synthesis, degradation, folding and metabolism. However, the exact functions of most DnaJ members are not fully understood in insects. Here, we identified three genes, AccDnaJA1, AccDnaJB12 and AccDnaJC8, in Apis cerana cerana and explored their connection with the environmental stress response. Quantitative real-time PCR results showed that the mRNA levels of AccDnaJA1, AccDnaJB12 and AccDnaJC8 were all induced under cold, UV, H2O2 and different pesticides treatment. The expression patterns of AccDnaJB12 and AccDnaJC8 were upregulated by CdCl2 and HgCl2 stress, while the transcriptional levels of AccDnaJA1 were downregulated by CdCl2 and HgCl2 stress. Western blot findings further indicated that AccDnaJB12 protein levels were increased by some stress conditions. Knockdown of each of these three genes downregulated the transcriptional patterns of several stress response-related genes at different levels. Functional analysis further demonstrated that the resistance of Apis cerana cerana to lambda-cyhalothrin stress was reduced with knockdown of AccDnaJA1, AccDnaJB12 or AccDnaJC8, indicating that these three genes may be involved in the tolerance to this pesticide. Taken together, these findings indicate that AccDnaJA1, AccDnaJB12 and AccDnaJC8 may play pivotal roles in the stress response by facilitating honeybee survival under some adverse circumstances. To our knowledge, this is the first report that reveals the roles of DnaJ family proteins under different adverse circumstances in Apis cerana cerana.